Equine infectious anemia in carthorses from urban areas of southern Brazil - João Henrique Perotta (Semina: Ciências Agrárias, 2015)
Equine infectious anemia (EIA) is an infectious viral disease caused by a Lentivirus , which affects equids worldwide. The disease has no currently treatment and euthanasia of infected animals is mandatory by the Brazilian Ministry of Agriculture, Livestock and Supply (MAPA) as basis for disease control. Carthorses are used to move daily throughout the cities with their owners to collect recycling materials. Considering the socio-economic importance of this group of horses, the aim of this study was to determine the infection rate of EIA virus in carthorses from urban areas of Curitiba and surroundings. The detection of anti-EIA virus antibodies was performed by the agar gel immunodiffusion test (AGID). One out of 97 (1.03%) horse was positive for EIA. Active surveillance programs are crucial for monitoring, prevention and control of infectious diseases, particularly in carthorses, which may act as disseminators of pathogens.